-36-3n=-6n-6(1-3n)

Simple and best practice solution for -36-3n=-6n-6(1-3n) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -36-3n=-6n-6(1-3n) equation:


Simplifying
-36 + -3n = -6n + -6(1 + -3n)
-36 + -3n = -6n + (1 * -6 + -3n * -6)
-36 + -3n = -6n + (-6 + 18n)

Reorder the terms:
-36 + -3n = -6 + -6n + 18n

Combine like terms: -6n + 18n = 12n
-36 + -3n = -6 + 12n

Solving
-36 + -3n = -6 + 12n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '-12n' to each side of the equation.
-36 + -3n + -12n = -6 + 12n + -12n

Combine like terms: -3n + -12n = -15n
-36 + -15n = -6 + 12n + -12n

Combine like terms: 12n + -12n = 0
-36 + -15n = -6 + 0
-36 + -15n = -6

Add '36' to each side of the equation.
-36 + 36 + -15n = -6 + 36

Combine like terms: -36 + 36 = 0
0 + -15n = -6 + 36
-15n = -6 + 36

Combine like terms: -6 + 36 = 30
-15n = 30

Divide each side by '-15'.
n = -2

Simplifying
n = -2

See similar equations:

| 140m+60n-160m-50n= | | [5n+12]+2=0 | | 2(c-5)=8c+2 | | 7u+7q-8= | | 6=(y+2) | | 8(-5-n)=-22+n | | 19x+24x+17x=180 | | 12-4b=4 | | 2(x+1)=7+2x | | 19x+24x=180 | | 4c-5d+2c-6d= | | -85=7x-8 | | 4(y+8)=0.5(4y-8) | | y+2x=40 | | 4x^3/3xy^-4 | | 0=16-3x-4y | | 13x+9=3x+9 | | -51=-2(1-5n)-(1-6m) | | x(6x-7)=o | | 5r^2-46r+48=0 | | 2q+3=11 | | 4a+2b+c=1000 | | 2x+8=2(1+2x) | | 5n^2+38n-63=0 | | -7c+4-c=-2(c+3) | | -2x(x+5)=3x-15 | | 0x+8=20 | | 4x-10=-4x | | N^2/2n-1 | | 3(3x+4)=3x+18 | | 10a=3.5(17) | | 2x+58=3(2+5x) |

Equations solver categories